2020
DOI: 10.1039/d0ra07286a
|View full text |Cite
|
Sign up to set email alerts
|

A KBr-impregnated paper substrate as a sample probe for the enhanced ATR-FTIR signal strength of anionic and non-ionic surfactants in an aqueous medium

Abstract: Flow diagram of the procedures for the analysis of surfactants using modified GFF paper substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The spectra of the formation of the Au-Ag core-shell composite nanoparticles were conrmed using the literature. 32,33,36 As shown in Fig. 7(e), aer the addition of L-cysteine into the bimetallic composite nanoparticle solution, the slight changes were observed in the spectra.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The spectra of the formation of the Au-Ag core-shell composite nanoparticles were conrmed using the literature. 32,33,36 As shown in Fig. 7(e), aer the addition of L-cysteine into the bimetallic composite nanoparticle solution, the slight changes were observed in the spectra.…”
Section: Resultsmentioning
confidence: 78%
“…In previous years, co-workers have exploited the use of FTIR for qualitative and quantitative analyses of biological and food samples, and various ionic species in the environment, based on the measurement of the selected characteristic absorption peaks of the analyte in the IR spectra. [32][33][34][35] In the present work, the preliminary investigations were performed with DRS-FTIR to determine the presence of the spectral bands of citrate-capped AuNPs and L-cysteine. Second, the freshly prepared standard solutions of dispersed and aggregated Au-Ag core-shell composite nanoparticles were analyzed to observe the characteristic IR absorption peaks of individual components, which were used to form bimetallic composite nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Except for glass microfiber filter paper, the quartz filter, Whatman filter, and xerox printing paper were found to be unsuitable since the very large pore size on their surface led to the incomplete trapping of the analytes within the fibers of the paper due to the rapid spreading of the liquid, resulting in a low color appearance. 43 Therefore, AuNPs were used for the multiresidue detection of metal ions (As( iii ) and Pb( ii )) using glass microfiber filter based paper sensor and colorimetry in environmental water samples.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our research group has been reported a KBr-impregnated paper substrate as a sample probe for the enhanced IR signal strength of surfactants in an aqueous medium with the same phenomenon. 43 TEM measurement was also performed to verify the actual size, shape, and morphologies of AuNPs/Glu before and aer the addition of As(III) and Pb(II) in aqueous solution. Fig.…”
Section: Mechanism For the Detection Of As(iii) And Pb(ii) Using Aunps/glu As The Chemical Sensormentioning
confidence: 99%
“…A recent development in this analytical technique is the use of paper substrate during the analysis. Kurrey et al ( 2020 ) proposed a paper-based KBr to replace the traditional KBr pellet as a sample holder.…”
Section: Analysis Of Surfactantsmentioning
confidence: 99%